THE LIFE AND WORK OF BENJAMIN TYAMZASHE, A CONTEMPORARY XHOSA COMPOSER, by Diedre D. Hansen. Occasional paper No. 11, Institute of Social and Economic Research, Rhodes University, Grahamstown, South Africa, 1968. Price 50 cents, pp. 33. Six musical illustrations. - Tracey, Andrew (International Library of African Music, 1969)
pages: 104
Keywords: South Africa; African Music